Design Thinking and Cognitive Walkthrough for Website User Experience Improvement - Umaroh, Sofia; Fitrianti, Nur; Rahayu, Astri; Ramadhan Putra, Kurnia (Jurnal Nasional Teknologi dan Sistem Informasi, 2024)
Desa Linggar located in the Rancaekek sub-district, Bandung Regency has implemented a website that functions as a medium of public information needed by the Desa Linggar community. In implementing the website, its user interface (UI) and user experience (UX) should accordance with the user's needs. However, the use of the Desa Linggar website is still not effective, especially in disseminating information to the Desa Linggar community because the UI/UX of the website is still less attractive. Thus, this study evaluates and improves the UI/UX on the Desa Linggar website using the design thinking method, cognitive walkthrough to test the prototype, UEQ (User experience Questionnaire) with the target respondent before repairing 45 respondents and the target after repairing 6 respondents and adopting the gestalt principle to design improvement method according to user psychology. The results of the research on the Desa Linggar website obtained a learning ability value of 90%, effectiveness of 0.10 or 10%, and efficiency of 0.02 with users completing 2% of each given task and evaluating the user experience of improvement using the UEQ questionnaire with an average value of scale. efficiency 2,583, stimulation 2,458, attractiveness 2,306, perspicuity 2,250, Dependability 2,125, and novelty 1,833 with â€œexcellentâ€ rate intervals.